Errance, sédentarité ou la naissance d'une ethnie prohibée: les Silmimoose du Burkina Faso - Lingane, Zakaria (Anthropologica, 2022)
Recent research has demonstrated difficulties in the definition of the ethnic realities which do not use the usual criteria: history, culture, language, genealogy and state bound aries. Based on the «ethnogenesis» of the Silmimoose (sing. Silmimoaga) of Burkina Faso, crossbreds between Moose (sing. Moaga) sedentary farmers and the Fulbe (Silmiise; sing. Silmiiga) semi-nomadic pastoralists, this essay tries to show the history of the concept of ethnicity and day-to-day life as seen by this community. The moaga state, known as a model of ethnogenetic mixing and interethnic integration, found its limits when it tried to integrate the Silmimoose. In many ways, the Silmimoose are considered a «forbidden» people. Here we wish to analyze the historical and ideological roots of this marginal ization by studying the moaga and silmiiga societies and in our final analysis to find out whether there has been a renewal of ethnic consciousness and how it came about or whether in fact the Silmimoose will remain the ethnic group shunned by the dominant cultures of the region.